Letter: evaluation and proposed reclassification of HCC prediction model of Tahata et al. in chronic hepatitis C genotype 4 patient. Authors' reply. Issue 2 (30th December 2021) - Tahata, Yuki; Sakamori, Ryotaro; Yamada, Ryoko; Kodama, Takahiro; Hikita, Hayato; Hagiwara, Hideki; Imai, Yasuharu; Hiramatsu, Naoki; Tamura, Shinji; Yamamoto, Keiji; Oshita, Masahide; Ohkawa, Kazuyoshi; et al.
LINKED CONTENT: This article is linked to Tahata et al papers. To view these articles, visit https://doi.org/10.1111/apt.16632 and https://doi.org/10.1111/apt.16704